Civil Liability of Directors and Board of Commissioners for Startup Bankruptcy from the Perspective of Indonesian Positive Law - Sukma Asmarandani Ramelan; Fence M. Wantu; Weny Almoravid Dungga (Jurnal Hukum Prasada, 2026)
Despite growing scholarly attention to corporate insolvency in Indonesia, the civil liability of startup directors and boards of commissioners remains inadequately theorized within the specific context of high-risk, innovation-driven enterprises. This study examines the construction of civil liability of directors and boards of commissioners in startup bankruptcy under Indonesian positive law, with particular focus on the proportional application of limited liability principles, the business judgment rule, and the supervisory function. Using a normative legal method with statutory and conceptual approaches, this study draws on Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 37 of 2004 concerning Bankruptcy and PKPU, the Civil Code, and relevant legal doctrines. Unlike prior studies that examine corporate insolvency broadly or through comparative frameworks, this research specifically interrogates the normative adequacy of existing instruments when applied to the startup ecosystem's distinctive risk profile. The findings indicate that civil liability of corporate organs is not automatic upon bankruptcy but is contingent upon proven fault or negligence causally linked to the insufficiency of bankruptcy assets. This confirms that Indonesian corporate law possesses a principled framework to distinguish normal business failure from governance failure. As a practical implication, this study recommends that courts and regulators adopt clearer evidentiary thresholds for applying Article 97 and Article 115 of the Company Law in startup contexts, and that startup governance guidelines be developed to operationalize the business judgment rule as a safeguard against disproportionate liability exposure thereby preserving Indonesia's innovation ecosystem without compromising accountability.